PENGARUH PERSEPSI SISWA MENGENAI KETERAMPILAN MENGAJAR, KOMPETENSI KEPRIBADIAN, DAN KOMPETENSI SOSIAL GURU, TERHADAP PRESTASI BELAJAR SISWA PROGRAM STUDI ADMINISTRASI PERKANTORAN DI SMK NEGERI 1 PURWODADI - Rohmah, Kholifatul Kurnia; Marimin, Marimin (Fakultas Ekonomi, Universitas Negeri Semarang, 2015)
The purpose of this study is to determine either simultaneously or partially teaching skills teacher, personal competence, and sosial competence of techer on student achievement at tenth grade of SMK N 1 Purwodadi. The Population in this research is tenth grade AP as many as 117 students. The Variables were examined in this study are teaching skills teacher, personal competence, and sosial competence of teacher. Data collection is used by the writer are questionnaires, tests, observation and documentation. Data analyzed using descriptive analysis and multiple regression analysis. Results of this research multiple regression analysis is Y =56,484 + 0,138X1 + 0,118X2 + 0,154X3. There is a simultaneous effect of 58,2%, while the partial effect of teaching skills teacher by 22,09%, personal competence by 17,05%, and amounted to 7,23% of sosial competence.